Analysis of the Influence of Online Promotion, Service Quality, and Price on the Sustainability of Culinary MSMEs - Tiva Rochana; Dwiyani Sudaryanti; Siti Asiyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyse the influence of online promotion, service quality, and price on the sustainability of culinary MSMEs in Dodolan Kampung, Lumajang. This study also aims to identify the most dominant factor influencing business sustainability among the three variables. This study uses a quantitative approach with a survey method through a structured questionnaire. The research sample consists of 80 respondents who are MSME consumers participating in Dodolan Kampung, with a non-probability sampling technique. The data was analyzed using multiple linear regression to test the effect of online promotion, service quality, and price on MSME sustainability. The results show that service quality and price have a positive and significant effect on the sustainability of culinary MSMEs in Dodolan Kampung. However, online promotion does not show a significant effect. Of the three variables tested, service quality is the most dominant factor in supporting business sustainability. This study contributes theoretically by presenting empirical evidence on the sustainability of culinary MSMEs from a marketing perspective, particularly in the context of local community-based initiatives such as Dodolan Kampung. The findings of this study challenge common assumptions about the effectiveness of digital promotion, showing that service quality and price play a more important role than online promotion in small-scale businesses in non-urban areas. This study implies that MSME players need to optimize digital promotion, improve service quality, and implement value-based pricing strategies to maintain business sustainability. For policymakers, these findings can serve as a basis for designing digital marketing and customer service training programs and providing policy support that promotes the sustainable competitiveness of MSMEs. This study has limitations in terms of geographical scope, as it only covers culinary MSMEs in Banguntapan District, so the results cannot be generalized to other regions or different MSME sectors. In addition, the quantitative approach used does not explore in depth qualitative factors such as motivation, business culture, and customer relationship dynamics that may also influence MSME sustainability